Supply Chain Digitalization Strategy for Coconut Shell Charcoal to Reduce the Risk of Loss in International Trade - Rahardjo, Stephanie Audrey; Harahap, Nafisah Rahmadani; Olifia, Jessica (Journal of Applied Business Administration, 2024)
International business involves trade activities conducted between countries. To ensure the production of the best products, a company must have effective supply chain management. Digitalization is being widely adopted as a solution to address the challenges in international trade, keeping pace with technological advancements. This research aims to analyze the financial risks arising from the effectiveness of supply chain management in a company that produces coconut shell charcoal, utilizing digitalization. The research methodology includes a literature review, drawing data from various expert sources and readings. The findings of this research identify the challenges faced by coconut shell charcoal companies in their international supply chains and propose digitalization strategies to minimize financial risks. The results demonstrate that leveraging digital technology can enhance operational efficiency, reduce logistical barriers, and improve responsiveness to market demands. Implementing digitalization strategies offers significant benefits by enhancing overall company performance and customer satisfaction levels.